Prognostic value of preoperative chemotherapy for thymic epithelial tumors: A propensity-matched analysis based on the SEER database - Fan, Yan; Cui, Tianjiao; Wei, Shuai; Gao, Xingcai (Frontiers in Surgery, 2023)
Background: The aim of this study was to assess the impact of preoperative chemotherapy on long-term survival (≥1 month) in patients with thymic epithelial tumors (TETs) and conditions suitable for chemotherapy using data from surveillance, epidemiology, and end-result databases. Methods: This retrospective study controlled for confounding factors by propensity score matching (PSM), analyzed overall survival (OS) and cancer-specific survival (CSS) by Kaplan-Meier methods, and analyzed factors affecting the prognosis of patients undergoing surgery for thymic epithelial tumors by univariate and multifactorial Cox regression. Results: A total of 2,451 patients who underwent surgery for TETs were identified from the Surveillance, Epidemiology, and End Results database. Preoperative chemotherapy significantly improved OS and CSS in patients with stage III/IV TETs compared to patients without preoperative chemotherapy. Subgroup analysis showed that patients younger than 60 years of age with TETs, patients with thymic carcinoma, and patients with TETs with multiple cancers were more likely to benefit from preoperative chemotherapy. Conclusion: This study found that preoperative chemotherapy is a viable option for advanced thymoma with favorable overall and cancer-specific survival rates, but patient history and physical condition should be fully considered in conjunction with diagnostic imaging findings to assess patient tolerance to chemotherapy.